"Painful, yet Beautiful, Moments": Pathways Through Infant Feeding and Dynamic Conceptions of Breastfeeding Success. (January 2022) - Whipps, Mackenzie D. M.; Yoshikawa, Hirokazu; Demirci, Jill R.; Hill, Jennifer
What is breastfeeding "success"? In this article, we challenge the traditional biomedical definition, instead centering visions of success described by breastfeeding mothers themselves. Using semi-structured interviews, quantitative surveys, and written narratives of 38 first-time mothers in the United States, we describe five common pathways through the first-year postpartum, a taxonomic distinction far more complex than a success–failure dichotomy: sustained breastfeeding, exclusive pumping, combination feeding, rapid weaning, and grinding back to exclusivity. We also explore the myriad ways in which mothers define and experience breastfeeding success, and in the process uncover the ways that cultural narratives—especially intensive mothering —color those experiences. Finally, we discuss how these experiences are shaped by infant feeding pathway. In doing so, we discover nuance that has gone unexplored in the breastfeeding literature. These findings have implications for supporting, promoting, and protecting breastfeeding in the United States and other high-income countries.